PENGARUH KINERJA KEUANGAN TERHADAP NILAI PERUSAHAAN : KEBIJAKAN DIVIDEN SEBAGAI VARIABEL MODERATING - Rochmah, Siti Ainur; Fitria, Astri (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2017)
The purposes of this research are 1) to find out the significant influence of liquidity, leverage andprofitability to the firm value; 2) to find out the influence of dividend policy in the correlation of liquidity,leverage and profitability to the firm value.Population is allreal estate and property companies which are listedin Indonesia Stock Exchange in 2011-2014 periods. The sample collection technique has been done by usingpurposive sampling method, therefore 18 real estate dan property companies. The data analysis technique hasbeen carried out by using Moderated Regression Analysis and hypothesis test has been done by using SPSS 20version. Based on the hypothesis result test shows that; 1) Liquidity does not have any significant influence butpositive to the firm value, 2) dividend policy does not have any significant to moderate the liquidity influence tothe firm value, 3) Leverage has significant negative influence to the firm value, 4) dividend policy is significantlyable to moderate the leverage influence to the firm value, 5) Profitability has significant positive influence to thefirm value, 6) dividend policy is significantly moderate the profitability influence to the firm value.Keywords: Liquidity, leverage, profitability, dividend policy, firm value.